2003
DOI: 10.1073/pnas.0730735100
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus 1 activates cdc2 to recruit topoisomerase IIα for post-DNA synthesis expression of late genes

Abstract: A subset (␥2) of late herpes simplex virus 1 genes depends on viral DNA synthesis for its expression. For optimal expression, a small number of these genes, exemplified by U S11, also requires two viral proteins, the ␣ protein infected cell protein (ICP) 22 and the protein kinase U L13. Earlier we showed that UL13 and ICP22 mediate the stabilization of cdc2 and the replacement of its cellular partner, cyclin B, with the viral DNA polymerase processivity factor U L42. Here we report that cdc2 and its new partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
37
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 33 publications
4
37
0
1
Order By: Relevance
“…In recent studies, it has been shown that the expression of glycoprotein C and U S 11 is enhanced by the ICP22-mediated interaction of the viral DNA processivity factor U L 42 (a viral functional homologue of proliferating cell nuclear antigen), cyclin-dependent kinase cdc2, and topoisomerase IIa (34)(35)(36). One hypothesis that could explain the mechanism of activation of late promoters and the role of ionizing radiation in inducing these promoters is that these are activated by modifications in the structure of the DNA, either as a result of nicks, gaps, or other perturbations in the DNA structure.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it has been shown that the expression of glycoprotein C and U S 11 is enhanced by the ICP22-mediated interaction of the viral DNA processivity factor U L 42 (a viral functional homologue of proliferating cell nuclear antigen), cyclin-dependent kinase cdc2, and topoisomerase IIa (34)(35)(36). One hypothesis that could explain the mechanism of activation of late promoters and the role of ionizing radiation in inducing these promoters is that these are activated by modifications in the structure of the DNA, either as a result of nicks, gaps, or other perturbations in the DNA structure.…”
Section: Discussionmentioning
confidence: 99%
“…A key function expressed by the carboxyl-terminal domain (CTD) of ICP22 in conjunction with the viral U L 13 protein kinase is to enhance the synthesis of a subset of late (␥ 2 ) proteins exemplified by the products of the U L 38, U L 41, and U S 11 genes (2,24,31,37). In earlier studies, this laboratory reported that ICP22 and the U L 13 protein kinase mediate the activation of cdc2 and degradation of its partners, cyclins A and B (3,4). cdc2 and its new partner, the viral DNA polymerase accessory factor (U L 42), bind topoisomerase II␣ in an ICP22-dependent manner (1,4).…”
mentioning
confidence: 99%
“…In earlier studies, this laboratory reported that ICP22 and the U L 13 protein kinase mediate the activation of cdc2 and degradation of its partners, cyclins A and B (3,4). cdc2 and its new partner, the viral DNA polymerase accessory factor (U L 42), bind topoisomerase II␣ in an ICP22-dependent manner (1,4). In addition, ICP22 and U L 13 mediate an intermediate phosphorylation of the carboxyl terminus of RNA polymerase II (Pol II) in Vero cells (14,18,34,35).…”
mentioning
confidence: 99%
“…However, the experiments also raise the possibility that the action of pp71 is indirect. The HSV-1 IE proteins ICP22 and ICP27, encoded by US1 and UL54, respectively, have each been implicated in transcriptional regulation (1,34,58,63,64); thus, it could be these proteins that mediated the long-term expression, either alone or in combination with pp71. To resolve whether this was the case, derivatives of in1312 with an additional deletion of US1 or UL54 were constructed.…”
mentioning
confidence: 99%